2021
DOI: 10.1021/acs.organomet.0c00766
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-Free Hydrosilylation of Alkenes Catalyzed by Well-Defined Low-Valent Cobalt Catalysts

Abstract: A solvent-free cobalt-catalyzed highly selective hydrosilylation of alkenes has been developed. It was found that both Co­(PMe3)4 and CoCl­(PMe3)3 are highly active catalysts for hydrosilylation of alkenes. The former promoted Markovnikov-type hydrosilylation of the aryl alkenes, while the latter catalyzed anti-Markovnikov-type hydrosilylation of the alkyl alkenes. These two catalytic systems tolerate a variety of functional groups and provide high selectivity and medium to high yield. In the exploration of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Co(PMe 3 ) 4 accelerated Markovnikov hydrosilylation of vinyl arenes, while CoCl-(PMe 3 ) 3 catalyzed anti-Markovnikov hydrosilylation of aliphatic olefins. 20 We also found that both activity than the Co(III) complex for the selective hydrosilylation of alkenes. 21 In addition, our study demonstrates that both [PSiP] pincer Co(I) and Co(III) complexes exhibit good catalytic activity for alkene hydrosilylation reactions.…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…Co(PMe 3 ) 4 accelerated Markovnikov hydrosilylation of vinyl arenes, while CoCl-(PMe 3 ) 3 catalyzed anti-Markovnikov hydrosilylation of aliphatic olefins. 20 We also found that both activity than the Co(III) complex for the selective hydrosilylation of alkenes. 21 In addition, our study demonstrates that both [PSiP] pincer Co(I) and Co(III) complexes exhibit good catalytic activity for alkene hydrosilylation reactions.…”
Section: Introductionmentioning
confidence: 56%
“…In 2021, we utilized Co­(PMe 3 ) 4 and CoCl­(PMe 3 ) 3 as catalysts to realize olefin hydrosilylation with high selectivity and yield. Co­(PMe 3 ) 4 accelerated Markovnikov hydrosilylation of vinyl arenes, while CoCl­(PMe 3 ) 3 catalyzed anti -Markovnikov hydrosilylation of aliphatic olefins . We also found that both [P, C] – chelate Co­(I) and Co­(III) complexes could catalyze alkene hydrosilylation reactions, and the Co­(I) complex exhibited more activity than the Co­(III) complex for the selective hydrosilylation of alkenes …”
Section: Introductionmentioning
confidence: 71%
“…71 Shortly thereafter, Deming used the same cobalt(0) complex Co-27 as an efficient initiator for the controlled polymerization of αamino acid-N-carboxyanhydrides (NCAs) (Scheme 24b), 72 a procedure that is still used by this group for their numerous works in this field. More recently, Co(PMe 3 ) 4 (Co-27) has also been reported as an efficient catalyst for the reduction of alkynes and alkenes through hydrophosphorylation 73 and hydrosilylation, 74 respectively (Scheme 24c). This well-defined cobalt complex also played an important role in bond activations.…”
Section: Cobalt(0)mentioning
confidence: 99%
“…In recent years, there are more and more reports on alkene hydrosilylation catalyzed by base metals such as iron, [4][5][6][7][8][9] cobalt [9][10][11][12][13][14][15][16][17] and nickel. [18][19][20][21][22] However, in the construction of a ligand skeleton, most catalysts are metal complexes supported by bidentate ligands 6,16,20 or pincer ligands ([NNN], 7,18,19 [NNP] 4,5 [CNC] 11 and [PSiP] 13,14 ).…”
Section: Introductionmentioning
confidence: 99%